PENYUSUNAN LAPORAN KEUANGAN DAN PERANAN PROFESI AKUNTANSI - Dewi, Syanti; Zebua, Lydia Patricia; Lorensa, Willsen (Jurnal Serina Abdimas, 2024)
Preparing financial reports is an important process in company financial management that involves collecting, classifying and presenting financial information. The preparation of this report must follow generally accepted accounting principles or have relevant accounting standards according to the jurisdiction. The financial report itself has the function of presenting financial information that is relevant, can be trusted to stakeholders regarding the financial performance of a company, and can be used in decision making. The accounting profession plays a key role in ensuring the accuracy, relevance and integrity of financial reports. The accounting profession also helps maintain transparency and accountability in financial reporting. It is expected to help students, so that after graduating from high school they can immediately work and directly apply the knowledge gained at school into practice. This activity is held face to face, so that it is easy for us to provide training to Bunda Hati Kudus High School students majoring in Social Sciences class 12 (twelve), in explaining financial report material according to applicable standards, as well as insight into the accounting profession and its role in managing finances. The specific objective of this training is to provide useful elements for all transactions and events that occur during a period in the service undertaking as well as the profession itself. The results of community service activities provide results in growing their interest in continuing to college, especially accounting majors, where all work can be easier.